2002
DOI: 10.1007/s00221-002-1133-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention to pain: a psychophysical investigation

Abstract: Laboratory research suggests that the processing of painful stimuli can be modulated by selective attention to a particular sensory modality. However, alternative accounts for previous findings remain possible in terms of task-switching and spatial attention effects. In the present study, we examined whether attention can be selectively directed to the pain modality in order to facilitate the processing of the sensory-discriminative aspects of painful laser heat stimuli when these alternatives were ruled out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 0 publications
2
48
1
2
Order By: Relevance
“…These physiological findings highlight the efficacy of our attentional manipulation, whereby subjects attended more to odor content when it was relevant for the task (odor attention) than when it was irrelevant (tone attention). Moreover, the data are compatible with previous work showing that human can selectively direct their attention to the olfactory modality (Spence et al, 2001;Zelano et al, 2005).…”
Section: Behavioral and Physiological Datasupporting
confidence: 90%
See 1 more Smart Citation
“…These physiological findings highlight the efficacy of our attentional manipulation, whereby subjects attended more to odor content when it was relevant for the task (odor attention) than when it was irrelevant (tone attention). Moreover, the data are compatible with previous work showing that human can selectively direct their attention to the olfactory modality (Spence et al, 2001;Zelano et al, 2005).…”
Section: Behavioral and Physiological Datasupporting
confidence: 90%
“…This prevalent view, based primarily on olfactory anatomical evidence from rodents and nonhuman primates, stands in conflict with the strong attentional effect on sniffing behavior observed in our experiment, along with increasing psychophysical data showing that humans can successfully divert their attention between olfactory and nonolfactory modalities, implying a mechanism common to all sensory systems (Spence et al, 2001;Zelano et al, 2005). Our results provide solid neurobiological evidence supporting the functional integrity of an olfactory thalamocortical pathway when a subject attends to odor.…”
Section: Discussioncontrasting
confidence: 63%
“…Again it should be noted that the effects in this study do not necessarily reflect perceptual changes but might also be explained by criterion shifting and response biases (Spence et al, 2004). In another study using a cueing paradigm, Spence et al (2002) instructed healthy participants to make spatial discriminations of visual and pain stimuli presented on the left arm. Each stimulus was preceded by a symbolic cue correctly (67%) or incorrectly (33%) signalling the modality for the upcoming stimulus.…”
Section: Until Now Most Studies Investigating the Effects Of Intentimentioning
confidence: 74%
“…In contrast with the studies by Van Damme et al (2002 there was no difference between responses to pain targets and visual targets, suggesting that the goal to detect nociceptive input was not prioritized over the goal to detect visual input. However, this might be explained by the use of predictive cues in the study of Spence et al (2002), resulting in a ceiling of the cueing effects and thereby leaving no further room for differences between pain trials and visual trials.…”
Section: Until Now Most Studies Investigating the Effects Of Intentimentioning
confidence: 99%
“…In a recent psychophysiological study participants showed greater responses to an expected pain modality than to an unexpected one. 57 An underlying mechanism for the selective effects may be the more extensive involvement of autonomic and affective brain modulation in visceral stimulation and the bias towards spatial encoding in somatic stimulation. 58,59 An illustration of this is the greater activation of the nucleus cuneiformis, a nucleus of the brainstem reticular formation, during visceral pain than during somatic pain in a recent human fMRI study.…”
Section: Discussionmentioning
confidence: 99%